Relationship between endurance field tests and match performance in young soccer players - Castagna, C.; Manzi, V.; Impellizzeri, F.; Weston, M.; Barbero-Alvarez, J. C. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to examine the relationship between popular endurance field tests and physical match performance in elite male youth soccer players. Eighteen young male soccer players (age 14.4 ± 0.1 years, height 1.67 ± 4.8 cm, body mass 53.6 ± 1.8 kg) were randomly chosen among a population of elite-level soccer players. Players were observed during international championship games of the corresponding age categories and randomly submitted to the level 1 of the Yo-Yo intermittent recovery test (Yo-Yo IR1), the Multistage Fitness Test (MSFT), and the Hoff test on separate occasions. Physical and physiological match demands were assessed using Global Positioning System technology and short-range telemetry (GPS Elite, Canberra, Australia), respectively. Players covered 6,087 ± 582 m (5,098-7,019 m) of which 15% (930 ± 362 m; 442-1,513) were performed as a high-intensity activity. During the first and second halves, players attained 86.8 ± 6.5 and 85.8 ± 5.8% of maximum heart rate (HRmax; p = 0.17) with peak HRs of 100 ± 2 and 99.4 ± 3.2% of HRmax, respectively. Players' Yo-Yo IR1 and MSFT performance were significantly related (r = 0.62-0.76) to a number of match physical activities. However, the Hoff test was only significantly related with sprint distance (r = 0.70, p = 0.04). The Yo-Yo IR1 showed a very large association with MSFT performance (r = 0.89, p < 0.0001). The results of this study showed that the Yo-Yo IR1 and MSFT may be regarded as valuable tests to assess match fitness and subsequently guide training prescription in youth soccer players. The very strong relationship between Yo-Yo IR1 and MSFT suggests their use according to the period of the season and the aerobic fitness level of the players. Because of the association of the Yo-Yo IR1 and MSFT with match physical performances, these tests should be considered in talent selection and development of players.